A Large Palindrome With Interchromosomal Gene Duplications in the Pericentromeric Region of the D. melanogaster Y Chromosome. - Méndez-Lago, M.; Bergman, C.M.; de Pablos, B.; Tracey, A.; Whitehead, S.L.; Villasante, A. (Molecular Biology and Evolution, 2011)
The non-recombining Y chromosome is expected to degenerate over evolutionary time, however, gene gain is a common feature of Y chromosomes of mammals and Drosophila. Here, we report that a large palindrome containing interchromosomal segmental duplications is located in the vicinity of the first amplicon detected in the Y chromosome of D. melanogaster. The recent appearance of such amplicons suggests that duplications to the Y chromosome, followed by the amplification of the segmental duplications, are a mechanism for the continuing evolution of Drosophila Y chromosomes.